Role of rehabilitation in patients with chronic obstructive pulmonary disease - Zeinb M.M. El Dardery; Abdelhfeez Moshrif; Ibrahim M. Shalan; Yasin A. Gala (Al-Azhar Assiut Medical Journal)
Background and aim Chronic obstructive pulmonary disease (COPD) is recognized as a frequent, treatable, and preventable condition distinguished by persistent respiratory symptoms. This investigation aimed to assess the efficacy of pulmonary rehabilitation in enhancing dyspnea, exercise capacity, quality of life, and functional ability in cases with CPOD. Patients and methods This randomized controlled clinical trial has been conducted on eighty cases with stable CPOD, aged 40–75 years, of either sex, at the Chest Department of Al-Azhar University Hospitals in Assiut. The training regimen persisted for 6 weeks. Results Regarding post-treatment pulmonary function tests, there were statistically insignificant distinctions regarding pulmonary function tests P value greater than 0.05. Regarding baseline and follow-up arterial blood gases, a statistically significant difference was detected among PaO2 post, PaO2 pre, and regarding group 1A, 1B, 2A, and 2B P less than 0.05. While a statistically insignificant distinction was observed among PaCO2 pre, and PaCO2 post regarding group 1B, 1A, 2B, and 2A P greater than 0.05. Studying the difference between group 1A (received rehabilitation) and group 2A (did not receive Rehabilitation), in relation to bronchiectasis, we found a statistically significant variance was observed among both groups according to Pre 6-minute walking test, post-6-minute walking test and post modified Medical Research Council P less than 0.001, On the other hand, in relation to COPD without bronchiectasis a statistically significant variance was detected among both groups regarding following management modified Medical Research Council P less than 0.001. Conclusion Rehabilitation of COPD patients is an efficient tool in improving the life quality beside conventional medical treatment.